Growing Exclusive Breastfeeding on Relationships and Development in Infants Age 6-12 Months - Nela Novita Sari; Eva Chundrayetti; Yuliarni Syafrita (Science Midwifery, 2021)
Breast milk is the single best food for babies aged 0 6 months. For this reason, exclusive breastfeeding for infants aged 0-6 months is the right step to maximize growth and development in infants aged 0-6 months and growth and development at later ages, because babies get proper nutrition and reduce the risk of infectious diseases that can affect nutritional conditions and growing. This study aims to determine the relationship of exclusive breastfeeding to growth and development in infants aged 6-12 months. This type of research is descriptive analytic with a cross-sectional study approach. The population in this study were all infants aged 6-12 months, namely 1538 infants. Sampling using consecutive sampling technique with a sample size of 56 respondents. The results showed that there was no significant relationship between exclusive breastfeeding and growth based on body weight (p = 1,000) and growth based on head circumference (p = 0.743). There was a significant relationship between exclusive breastfeeding and growth based on body length (p = 0.027) and the development of infants aged 6-12 months (p = 0.013). It can be concluded that exclusive breastfeeding has a significant relationship with growth based on body length and development of infants aged 6-12 months. Therefore, it is expected that breastfeeding mothers always give exclusive breastfeeding to infants aged 0-6 months in order to maximize the baby's growth and development and growth and development at a later age.Breast milk is the single best food for babies aged 0 6 months. For this reason, exclusive breastfeeding for infants aged 0-6 months is the right step to maximize growth and development in infants aged 0-6 months and growth and development at later ages, because babies get proper nutrition and reduce the risk of infectious diseases that can affect nutritional conditions and growing. This study aims to determine the relationship of exclusive breastfeeding to growth and development in infants aged 6-12 months. This type of research is descriptive analytic with a cross-sectional study approach. The population in this study were all infants aged 6-12 months, namely 1538 infants. Sampling using consecutive sampling technique with a sample size of 56 respondents. The results showed that there was no significant relationship between exclusive breastfeeding and growth based on body weight (p = 1,000) and growth based on head circumference (p = 0.743). There was a significant relationship between exclusive breastfeeding and growth based on body length (p = 0.027) and the development of infants aged 6-12 months (p = 0.013). It can be concluded that exclusive breastfeeding has a significant relationship with growth based on body length and development of infants aged 6-12 months. Therefore, it is expected that breastfeeding mothers always give exclusive breastfeeding to infants aged 0-6 months in order to maximize the baby's growth and development and growth and development at a later age.